BUSINESS COMPETENCE COEFFICIENT-3CA - Argota-Pérez, Yadira (2021)
The aim of the study was to propose the coefficient of business competitiveness-3CA. The study was carried out from January to March 2021 where the ScienceDirect website was reviewed, introducing the following keywords in Spanish and English: model, coefficient, business competitiveness. 75 scientific articles were considered between the period 2015 to 2020 where 20 scientific journals were consulted. From the hermeneutical assessment of scientific publications, the coefficient of business competitiveness-3C is established, which considered three dimensions of capacity competencies variables: 1st) production, 2nd) marketing, and 3rd) recognizable income. Each dimension of capacity competence showed for its analysis, more than one indicator which were weighted in three levels: I) low (0.2; II), medium (0.6) and III) high (1.0). The coefficient of business competitiveness-3CA showed three ranges: 1st) 0.2-0.7; 2nd) 0.9-1.4 and 3rd) 2.3-3.4 where the first indicates that business competitiveness is insufficient, the second will be satisfactory, while the third is excellent. It is concluded that the coefficient of business competitiveness-3CA guarantees the excellence of processes and services from any factor that is intended to be analyzed in the indicators, since its weighting distinguishes the possibility that the company itself can be measured. Keywords: business competition – connection – productivity – society